Identification of Bacillus Spores by Matrix-Assisted Laser Desorption Ionization–Mass Spectrometry - Hathout, Yetrib (American Society for Microbiology, 1999)
Unique patterns of biomarkers were reproducibly characterized by matrix-assisted laser desorption ionization (MALDI)–mass spectrometry and were used to distinguish Bacillus species members from one another. Discrimination at the strain level was demonstrated for Bacillus cereus spores. Lipophilic biomarkers were invariant in Bacillus globigii spores produced in three different media and in B. globigii spores stored for more than 30 years. The sensitivity was less than 5,000 cells deposited for analysis. Protein biomarkers were also characterized by MALDI analysis by using spores treated briefly with corona plasma discharge. Protein biomarkers were readily desorbed following this treatment. The effect of corona plasma discharge on the spores was examined.